PENGARUH KUALITAS PELAYANAN, CITRA, DAN FUNGSI OTA (ONLINE TRAVEL AGENT) TERHADAP KEPUTUSAN TAMU MENGINAP DI MASA PANDEMI COVID-19 (Studi Kasus Pada Hotel Grand Dian Brebes) - Desy Rahmawati Lukmana; Haniek Listyorini; Ray Octafian; Hendrajaya Hendrajaya (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2023)
This research was conducted at the Grand Dian Hotel Brebes which aims to analyze and explain the influence of service quality, image and function of OTA (online travel agent) which is in poor condition due to lack of updates from OTA (Online Travel Agent) about hotel information, and prices from OTA (Online Travel Agent) is unstable. Research data obtained through questionnaires and interviews. The sample used in the study were 94 respondents. The research results are expected to provide useful information for management and employees. The data obtained were processed using descriptive analysis and quantitative statistical analysis. Quantitative analysis used multiple regression analysis to determine the effect of the independent variable on the dependent variable, test the model, test the hypothesis, and before doing the test, the validity and reliability tests were carried out first. The results of the regression analysis show that the increase in guest decisions to stay is directly influenced by the quality of service, image and function (online travel agent). The results of the multiple regression analysis test showed a significant F value, with a correlation value of determination adjusted R2 square of 0.610. This shows that the quality of service, image and function (online travel agent) significantly influence the decision of guests to stay together with a close relationship of 61.0%. This shows that to improve the decision of staying guests, it is necessary to improve the quality of service, as well as the image and function of a good OTA (online travel agent) in the eyes of the community, it will increase the decision of guests to stay in the next period.